(untitled) (Archives of Pediatrics of Uruguay, 2020)
Introduction: electrocardiograms (ECGs) are accessible, low cost tests, simple to perform at primary care level. Several studies have compared ECG readings made by family doctors and internists to those made by cardiologists and they have shown that the former have difficulties interpreting them. No studies were found that made such comparisons with pediatricians. Objective: assess the competence to read ECGs shown by pediatricians who had previously received conventional training. Material and methods: prior to the start of the study, a Pediatric Cardiologist trained Pediatricians to read and interpret ECGs in order to systematize the reading approach. Cross-sectional, prospective, double-blind study where two Pediatricians interpreted ECGs and were later assessed by a Pediatric Cardiologist. Pediatricians did not know the colleague’s readings or whose ECGs they were interpreting. An external researcher compared them. Authorization was requested from the General Management Department and from the Ethics Committee. Participation was voluntary, and prior informed consent was obtained. The population included ECGs of children aged between 5-15 years of old who attended the Pre-Assessment Sports Day. A pneumologist-cardiologist performed ECGs on 12 children. Materials: A pre-coded file was used to record the variables: heart rate, rhythm, p wave, PR interval, electric axis, QRS, QTc, T wave and ST segment. 60-110 bpm was considered a normal heart rate; PR interval 0.12-0.20 sec, QTC normal value between 0.33-0.44 sec. Results: the study analyzed results of 209 children and adolescents’ ECGs. There was 100% concordance between the rhythm and the electrical axis for the P wave. The concordance index exceeded 73% for all the variables and it reached a concordance of about 95%. However, for heart rate and QRS, although the Kappa point value can be considered acceptable, the confidence interval lower limits were lower than acceptable.